Impact of direct acting antiviral (DAA) treatment on glucose metabolism and reduction of pre-diabetes in patients with chronic hepatitis C - Weidner, Philip; Böttche, Dominik; Burgermeister, Elke; Teufel, Andreas; Ebert, Matthias; Antoni, Christoph Helmer (Journal of gastrointestinal and liver diseases, 2018)
BACKGROUND AND AIM: With the development of direct acting antiviral agents (DAA) chronic hepatitis C virus (HCV) infection has become curable in most patients. Since HCV infection is known to have direct and/or indirect effects on glucose metabolism, successful HCV treatment may have an impact in reducing glucose level, pre-diabetes, the need of treatment for diabetes, and ultimately diabetes-associated morbidity. We investigated the association of DAA treatment and glucose metabolism in the context of development or resolution of hepatic fibrosis in a large cohort of HCV- infected patients. - METHODS: In this retrospective single-center observational study, we investigated 281 patients receiving all-oral DAA therapy for fasting plasma glucose, HbA1c, liver enzymes and general clinical chemistry, measured during a 52-week follow-up. In addition, elastography, FIB-4- and APRI-calculation were used to assess hepatic fibrosis non-invasively. - RESULTS: Successful elimination of HCV through DAA treatment was associated with a significant drop in fasting glucose level and a reduced rate of impaired fasting plasma glucose (FPG). Interestingly, this metabolic change was BMI-independent. In addition, long-term glucose levels also decreased after successful DAA treatment. A significant APRI-score reduction was associated with a persistent improvement of FPG. However, DAA did not have an impact on glucose metabolism in patients suffering from liver cirrhosis. - CONCLUSION: This study highlights the beneficial impact of successful HCV therapy on glucose metabolism and identifies patients with liver cirrhosis as a collective in need of intensified surveillance with regard to diabetes progression despite HCV eradication.
Gesehen am 03.07.2019